Benefits and challenges of doing task-based language teaching in Indonesia: Teachers’ perception - Aninda Nidhomil Hima; Teguh Hadi Saputro; Rafika Rabba Farah (Universitas Muhammadiyah Malang, 2021)
Task-based language teaching (TBLT) has received significant attention from both researchers and practitioners of second language learning. This approach has been reported to be effective in various contexts. Studies on the teachers’ perception on TBLT have also been conducted. The results inform the perceived benefits and challenges of using TBLT in teaching context. However, very few studies have investigated the teachers’ perception in Indonesian context. To investigate the perception, a qualitative research design was employed. Three female English teachers of a vocational school in Malang, East Java, Indonesia were the participants of the study. Before the study was conducted, these three participants were asked to attend a training or coaching on TBLT. At the end of the training or coaching, they had to design a TBLT lesson plan which later were used in their real teaching to their students. After the whole training or coaching was finished, their perceptions about the perceived benefits and challenges about TBLT were investigated through focus-group-discussion (FGD) and individual interviews. The data were analyzed qualitatively and resulted in findings that fell into two categories, namely benefits and challenges. The benefits were this method (1) was considered to be the ‘right’ approach, (2) actively engaged the learners in their learning, (3) was relevant to the current curriculum, (4) increased the learners’ motivation and (5) provided “scaffolding” method for leaners’ use of the language and accomplish the tasks. Meanwhile, its challenges were (1) its time-consuming preparation, (2) complicated and confusing features of a task, (3) complicated implementation of the scaffolding process, (4) doubts or questions about “get-it-right-at-the-end approach” and (5) irrelevance of this method to the exam preparation.